DOI: 10.1007/978-3-540-73951-7_40
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Maximal Angles for Plane Straight-Line Graphs

Abstract: Let $G=(S, E)$ be a plane straight-line graph on a finite point set $S\subset\R^2$ in general position. The incident angles of a vertex $p \in S$ of $G$ are the angles between any two edges of $G$ that appear consecutively in the circular order of the edges incident to $p$. A plane straight-line graph is called $\phi$-open if each vertex has an incident angle of size at least $\phi$. In this paper we study the following type of question: What is the maximum angle $\phi$ such that for any finite set $S\subset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A somewhat simpler construction was subsequently proposed by Ackerman et al [1]. Aichholzer et al [2] have also obtained this result (together with additional related results), independently. However, in all these papers, the goal is to construct an α-ST (for α = π/3) and not an α-MST.The problem of computing an α-MST is similar in flavor to the problem of computing a Euclidean minimum weight degree-k spanning tree, which has been studied extensively (see, e.g., [4,10,15,16,18]).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…A somewhat simpler construction was subsequently proposed by Ackerman et al [1]. Aichholzer et al [2] have also obtained this result (together with additional related results), independently. However, in all these papers, the goal is to construct an α-ST (for α = π/3) and not an α-MST.The problem of computing an α-MST is similar in flavor to the problem of computing a Euclidean minimum weight degree-k spanning tree, which has been studied extensively (see, e.g., [4,10,15,16,18]).…”
mentioning
confidence: 66%
“…A somewhat simpler construction was subsequently proposed by Ackerman et al [1]. Aichholzer et al [2] have also obtained this result (together with additional related results), independently. However, in all these papers, the goal is to construct an α-ST (for α = π/3) and not an α-MST.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Related problems and results. Various angle conditions imposed on geometric graphs (graphs with straight-line edges) drawn on a given set of points have been studied in [3,4,5,6,12]. In particular, Fekete and Woeginger [12] have focused on rotation angles of Hamiltonian cycles and paths and raised many challenging questions.…”
Section: Introductionmentioning
confidence: 99%
“…Aichholzer et al [3] studied similar questions for planar geometric graphs. Among other results, they showed that any point set in general position in the plane admits a non-intersecting Hamiltonian (spanning) path with the property that each rotation angle is at most 3π/4.…”
Section: Introductionmentioning
confidence: 99%